Stabilization of the dystroglycan complex in Cajal bands of myelinating Schwann cells through plectin‐mediated anchorage to vimentin filaments. Issue 8 (9th July 2013) - Walko, Gernot; Wögenstein, Karl L.; Winter, Lilli; Fischer, Irmgard; Feltri, M. Laura; Wiche, Gerhard
<x xml:space="preserve">Abstract</x> Previous studies have unmasked plectin, a uniquely versatile intermediate filament‐associated cytolinker protein, to be essential for skin and skeletal muscle integrity. Different sets of isoforms of the protein were found to stabilize cells mechanically, regulate cytoskeletal dynamics, and serve as a scaffolding platform for signaling molecules. Here, we investigated whether a similar scenario prevails in myelinating Schwann cells. Using isoform‐specific antibodies, the two plectin variants predominantly expressed in the cytoplasmic compartment (Cajal bands) of Schwann cells were identified as plectin (P)1 and P1c. Coimmunoprecipitation and immunolocalization experiments revealed complex formation of Cajal band plectin with β‐dystroglycan, the core component of the dystrophin glycoprotein complex that in Schwann cells is crucial for the compartmentalization and stabilization of the myelin sheath. To study the functional implications of Schwann cell‐specific plectin‐β‐dystroglycan interaction, we generated conditional (Schwann cell‐restricted) plectin knockout mice. Ablation of plectin in myelinating Schwann cells (SCs) was found not to affect myelin sheath formation but to abrogate the tight association of the dystroglycan complex with the intermediate filament cytoskeleton. We show that the disruption of this association leads to the destabilization of the dystroglycan complex combined with increased myelin sheath deformations observed in the peripheral nerve during ageing of the animal. GLIA 2013;61:1274–1287